2014
DOI: 10.1371/journal.pone.0107853
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Glomerular and Tubulointerstitial Injuries by Dietary Salt Reduction with Combination Therapy of Angiotensin II Receptor Blocker and Calcium Channel Blocker in Dahl Salt-Sensitive Rats

Abstract: A growing body of evidence indicates that renal tissue injuries are reversible. We investigated whether dietary salt reduction with the combination therapy of angiotensin II type 1 receptor blocker (ARB) plus calcium channel blocker (CCB) reverses renal tissue injury in Dahl salt-sensitive (DSS) hypertensive rats. DSS rats were fed a high-salt diet (HS; 4% NaCl) for 4 weeks. Then, DSS rats were given one of the following for 10 weeks: HS diet; normal-salt diet (NS; 0.5% NaCl), NS + an ARB (olmesartan, 10 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 47 publications
3
14
0
Order By: Relevance
“…Significant hypertrophy occurs in several models of hypertension including the ANG II, 5/6 nephrectomy, and salt-sensitive hypertension models (3,23,17,30). Indeed, the concentration of ANG II in Bowman's space has been shown to be 1,000-fold higher than in the systemic circulation (36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant hypertrophy occurs in several models of hypertension including the ANG II, 5/6 nephrectomy, and salt-sensitive hypertension models (3,23,17,30). Indeed, the concentration of ANG II in Bowman's space has been shown to be 1,000-fold higher than in the systemic circulation (36).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we show that ANG II-induced glomerular hypertrophy was independent of blood pressure or hormonal status, suggesting a local role for ANG II in modifying renal architecture, separate from changes in blood pressure. Indeed, angiotensin receptor blocker administration in male Ren-2 transgenic rats can partially prevent glomerular volume expansion in the 5/6 nephrectomy model of hypertension (17), while the combination therapy of a calcium channel blocker (azelnidipine) and an angiotensin receptor blocker (olmesartan) given to male saltsensitive rats reduces mean glomerular area to a greater degree than when either is given alone (30). Interestingly, blood pressures in the treatment groups were also reduced, making it difficult to determine whether the reduction in glomerular area was a result of blood pressure normalization or a function of angiotensin receptor antagonism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…injury that was reversed by switching to a normal salt diet (Rafiq et al, 2014). In another report, it has been shown that, in an adenine-loaded rat, which is widely used as a model for renal failure, cessation of the adenine diet led to the reversal of renal damage (Shuvy et al, 2011).…”
Section: Induction Of Urinary Namentioning
confidence: 99%
“…Recently, Rafiq et al (2014) demonstrated that high-salt loading to Dahl salt-sensitive hypertensive rats induced renal Fig. 6.…”
Section: Induction Of Urinary Namentioning
confidence: 99%